Diagnóstico del nivel de competencias mediáticas audiovisuales en estudiantes, docentes y padres de familia de 23 instituciones educativas públicas, privadas y fiscomisionales de la ciudad de Loja, en las dimensiones: tecnología y lenguaje - Arévalo Hidalgo, María del Carmen (2015)
The rise of media and ICT, led to changes in society; and these changes are transforming expectations about what students should learn in a world of systems and communication networks and multimedia information. However, few investigations that are responsible for analyzing and diagnosing the degree of media literacy, with students and their immediate surroundings are parents and teachers. Therefore, it requires an analysis to assess the issue in a systematic way to provide better education starting with media literacy. The data obtained in this study suggest that teachers and parents have little knowledge in the use of technology in the teaching - learning, while students have a high level of familiarity with these tools, but do not know the use suitable. Thus, their poor ability to interact meaningfully with the media does not generate a social and cognitive progress. The data obtained will serve to be clear about the strengths and weaknesses that owns the media shows and from them to propose the implementation in the thematic curriculum that can be taught in the classroom are; thus, students will develop their audiovisual competence and may generate knowledge using technological innovations to support. Keywords: